Garra clavirostris, a new cyprinid fish (Teleostei: Cyprinidae: Labeoninae) from the Brahmaputra drainage, India - Roni, Narengbam; Sarbojit, Thaosen; Vishwanath, Waikhom (Zootaxa, 2017)
Garra clavirostris, a new cyprinid fish, is described from the Dilaima River, a tributary of the Brahmaputra in the Dima Hasao district, Assam. The new species is distinguished from all its congeners in northeast India in having a combination of the following characters: a prominent unilobed club-shaped proboscis overhanging the depressed rostral surface, with 5–9 medium to large uni- to multi-cuspid tubercles on the anterior margin and 5–6 uni- to multi-cuspid tubercles on the anteroventral marginal aspect; a prominent transverse lobe on the snout, with 17−25 small- to large-sized multicuspid tubercles; and presence of a black spot at the upper angle of the gill opening.